2006
DOI: 10.1080/07060660609507317
|View full text |Cite
|
Sign up to set email alerts
|

Differential production of sclerotia by isolates ofSclerotinia sclerotiorumfrom Alaska

Abstract: Sclerotinia sclerotiorum was isolated from lettuce (Lactuca sativa) grown in Alaska. Sections of cabbage (Brassica oleracea var. capitata) and lettuce were inoculated with isolates A and B. Sclerotia of S. sclerotiorum were counted and weighed after the host tissue decomposed. Isolate A produced a mean of 42 sclerotia weighing 1.9 g on 100 g of cabbage 'Balbro', which was twice the number of sclerotia and triple the biomass produced by isolate B. On three cultivars of lettuce, isolate A had a greater mass and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The number of sclerotia produced by S. sclerotiorum on different plant tissues is also variable and is an important factor in determining the inoculum levels in soil following an infected crop. For instance, an infected cabbage head was found to produce 250 to 500 sclerotia, (Leiner and Winton 2006) while an infected carrot root produced up to 30 (Jensen et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…The number of sclerotia produced by S. sclerotiorum on different plant tissues is also variable and is an important factor in determining the inoculum levels in soil following an infected crop. For instance, an infected cabbage head was found to produce 250 to 500 sclerotia, (Leiner and Winton 2006) while an infected carrot root produced up to 30 (Jensen et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…In the same work, the weight of sclerotia produced by two different S. sclerotiorum isolates on three different iceberg lettuce varieties was in the range of 14-26 mg. By comparison, an almost identical weight range for S. sclerotiorum sclerotia produced on lettuce (13-28 mg) was observed in the current study, but much smaller sclerotia were produced on carrot (12-14 mg), with the largest sclerotia produced on OSR (33-60 mg). Leiner & Winton (2006) also estimated that 250-500 sclerotia might be produced on a single iceberg lettuce plant depending on S. sclerotiorum isolate, which is substantially more sclerotia than observed on the infected butterhead lettuce in this work (55-122 per plant). However, this might be explained by iceberg lettuce forming a dense compact head similar to a cabbage, which would have a much greater biomass and hence sustain a greater level of sclerotial production than the open, leafy butterhead type of lettuce used here.…”
Section: Discussionmentioning
confidence: 50%
“…Interestingly, the three S. sclerotiorum isolates showed a consistent pattern of sclerotial production irrespective of crop type; L6 produced large numbers of small sclerotia while L44 produced small numbers of large sclerotia, with L17 intermediate between the two. Leiner & Winton () also observed that one of the two S. sclerotiorum isolates they examined consistently produced more sclerotia on cabbage, carrot, celery and lettuce tissue. As well as being more numerous, the sclerotia from this isolate were also larger.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations